Optimization Of Gas Turbine Performance 2.1 Using the Overhaul Combustion Inspection Method - Handoko, Susilo; Hendra, Hendra; Suharyadi, Hafid; Widiyanto, Totok (Politeknik Negeri Lhokseumawe, 2024)
Gas turbines are one type of internal combustion drive, the initial mover utilizes gas combustion as a fluid to rotate the turbine with internal combustion. Gas turbines at private companies producing electricity use the initial movers, namely gas turbines and steam turbines. Therefore, it is also called the